Analysis of price discovery and non-linear dynamics between volatility index and volatility index futures. Issue 3 (1st September 2016) - Lee, Yen-Hsien; Mo, Wan-Shin
ABSTRACT: This study utilises a smooth transition vector error correction model with a Generalised AutoRegressive Conditional Heteroskedasticity GARCH model to investigate the price-discovery and non-linear dynamics at different times when a deviation occurs in the co-movement equilibrium between the spot volatility index (VIX) and futures. Our results show support for relative price-discovery contribution from both VIX spot and VIX futures markets. Moreover, we provide evidence that information traders obtain profits by exhibiting more confidence in exploiting large deviations from the equilibrium in these two markets, whereas noise traders expand their mispricing behaviour. Both VIX spot and VIX futures in turn continue to deviate from equilibrium with the existence of large deviations from the co-movement.